1888-89 Ala. Laws 82 - (:unkn) unknown (My University, 1889)
Prohibited associating, assembling, congregating together for the purpose of drilling, parading, or marching, or bearing arms in such capacity. Violators guilty a misdemeanor & fined not more than one thousand dollars.
Keywords: MILITIAS